Recurrent Candida albicans Ventriculitis Treated with Intraventricular Liposomal Amphotericin B - Demet Toprak; Sevliya Öcal Demir; Eda Kepenekli Kadayifci; Özden Türel; Ahmet Soysal; Mustafa Bakir (Case Reports in Infectious Diseases)
Central nervous system (CNS) infection with Candida is rare but significant because of its high morbidity and mortality. When present, it is commonly seen among immunocompromised and hospitalized patients. Herein, we describe a case of a four-year-old boy with acute lymphoblastic leukemia (ALL) who experienced recurrent Candida albicans meningitis. The patient was treated successfully with intravenous liposomal amphotericin B at first attack, but 25 days after discharge he was readmitted to hospital with symptoms of meningitis. Candida albicans was grown in CFS culture again and cranial magnetic resonance imaging (MRI) showed ventriculitis. We administered liposomal amphotericin B both intravenously and intraventricularly and favorable result was achieved without any adverse effects. Intraventricular amphotericin B may be considered for the treatment of recurrent CNS Candida infections in addition to intravenous administration.